Online Buying Interest in the Ciayumajakuning Property Industry from the Influence of Organic and Non-Organic Digital Marcom - Rival Rivaldi; Dimas Faturrahman; Misbak Misbak; Tiara Muthiarsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study wants to find out if using free Live Streaming and paid Meta Ads to market online works to make people want to buy property in the Ciayumajakuning area. We got information from 270 people using online surveys, and we used math to look at the information. The study shows that both ways work to make people want to buy online, but Meta Ads works a little better. Live Streaming, however, enhances consumer trust through real-time interaction and product visualization. This research offers practical insights for property marketers in selecting adaptive and effective digital strategies based on campaign goals, consumer behavior, and resource allocation.